Evaluation of CYP2C19 Genotype‐Guided Voriconazole Prophylaxis After Allogeneic Hematopoietic Cell Transplant. Issue 3 (26th October 2019) - Patel, Jai N.; Hamadeh, Issam S.; Robinson, Myra; Shahid, Zainab; Symanowski, James; Steuerwald, Nury; Hamilton, Alicia; Reese, Emily S.; Plesca, Dragos C.; Arnall, Justin; Taylor, Margaret; Trivedi, Jigar; et al.
Abstract : There is a high risk of voriconazole failure in those with subtherapeutic drug concentrations, which is more common in CYP2C19 (cytochrome P450 2C19) rapid/ultrarapid metabolizers (RMs/UMs). We evaluated CYP2C19 genotype‐guided voriconazole dosing on drug concentrations and clinical outcomes in adult allogeneic hematopoietic cell transplant recipients. Poor (PMs), intermediate (IMs), and normal metabolizers (NMs) received voriconazole 200 mg twice daily; RMs/UMs received 300 mg twice daily. Steady‐state trough concentrations were obtained after 5 days, targeting 1.0–5.5 mg/L. Of 89 evaluable patients, 29% had subtherapeutic concentrations compared with 50% in historical controls ( P  < 0.001). Zero, 26%, 50%, and 16% of PMs, IMs, NMs, and RMs/UMs were subtherapeutic. Voriconazole success rate was 78% compared with 54% in historical controls ( P  < 0.001). No patients experienced an invasive fungal infection (IFI). Genotype‐guided dosing resulted in $4, 700 estimated per patient savings as compared with simulated controls. CYP2C19 genotype‐guided voriconazole dosing reduced subtherapeutic drug concentrations and effectively prevented IFIs.